Investigation on the performance of crushed tires as cement replacement in concrete - Wan Mohammad, Wan Ahmad Soffian; Abas, Nor Haslinda; Shahidan, Shahiron (Penerbit UTHM, 2020)
The automobile has become an indispensable means of transportation for many households throughout the world. Thus, the disposal of vehicle tires represents a major environmental issue. Globally, more than 330 million tires are discarded every year and accumulated over the years in different countries [1]. In Malaysia, an estimated 150,000 tonnes of waste tires per year are dumped illegally. The disposal and reprocessing of tires are difficult since they contain complex mixtures of different materials such as rubber, carbon black, steel cord and other organic and inorganic minor components ..